Use of 3 Months Injectable Family Planning Against Weight Gain of Family Planning Acceptors in Mangga Village, Medan Tuntungan Subdistrict in 2019 - Arva Rochmawati; Nurdiana Manurung (Institute of Computer Science (IOCS), 2019)
The purpose of this research is to provide useful information and input for the community or mothers of 3-month injectable family planning injections, and to provide services and counseling, especially to 3-month injection family planning acceptors in dealing with weight gain in Mangga Village, Medan Tuntungan District. Increasing the knowledge of mothers of 3-month injection KB acceptors about the use of KB which can increase weight gain in Mangga Village, Medan Tuntunga Subdistrict. the type and form of activity of this activity is as a provision of counseling materials to mothers of 3-month injection KB acceptors. teach mothers who accept 3 months of injectable family planning how to prevent weight gain during the use of 3 months of injectable family planning. To achieve the objectives of the above activities, activities were carried out, including providing counseling materials about explaining the meaning, benefits, advantages and disadvantages of 3-month injection KB to mothers who accept 3-month injections in Mangga Village, Medan Tuntungan District.